Comparative Genomics of Plasmid-Bearing Staphylococcus aureus Strains Isolated From Various Retail Meats - Karki, Anand B.; Neyaz, Leena; Fakhr, Mohamed K. (Frontiers in Microbiology, 2020)
Food poisoning due to the consumption of Staphylococcus aureus contaminated food is a major health problem worldwide. In this study, we sequenced the genomes of ten plasmid-bearing S. aureus strains isolated from retail beef, chicken, turkey, and pork. The chromosomes of the strains varied in size from 2,654,842 – 2,807,514 bp, and a total of 25 plasmids were identified ranging from 1.4 - 118 kb. Comparative genomic analysis revealed similarities between strains isolated from the same retail meat source, indicating an origin-specific genomic composition. Genes known to modulate attachment, invasion, and toxin production were identified in the 10 genomes. Strains from retail chicken resembled human clinical isolates with respect to virulence factors and genomic islands, and retail turkey and pork isolates shared similarity with S. aureus from livestock. Most chromosomes contained antimicrobial resistance, heavy metal resistance, and stress response genes, and several plasmids contained genes involved in antimicrobial resistance and virulence. In conclusion, the genomes of S. aureus strains isolated from retail meats showed an origin-specific composition and contained virulence and antimicrobial resistance genes similar to those present in human clinical isolates.